Kuantifikasi Vitamin C Petai Cina (Leucaena leucocephala) dengan Spektrofotometri UV-Vis - Asti Pratiwi; Aminah Syarifuddin; Cucu Arum Dwi Cahya; Sri Rahayu (Jurnal Indah Sains dan Klinis, 2023)
Background: Vitamin C is very soluble in water and is always used for additional nutrition in the form of supplements. This vitamin is needed by the body because it can increase the body's ability to fight disease and function as a neutralizer of radical particles found in the body, usually referred to as antioxidants. One of them is the Petai Cina plant which is used by the community as a savory flavor in dishes, and can also be used as traditional medicine. Objective: To determine the presence and levels of vitamin C in Petai Cina in the Lubuk Pakam regional market. with quality and quantity analysis. Method: Samples were analyzed qualitatively using a specific color reagent for vitamin C and quality was determined using UV spectrophotometry. Results: The standard vitamin C wavelength is 224.5 nm at a concentration of 4 ppm with the regression equation y = 0.0339x + 0.3922. Qualitatively, it is proven that there is vitamin C in Petai Cina with a quantity of 0.1095 mg/mL. Conclusion: Vitamin is found in Petai Cina with a quantity of 0.1095 circulating in the Lubuk Pakam market